Coronal plane laxity of valgus osteoarthritic knee. (18th March 2019) - McAuliffe, Michael J; Garg, Gautam; Orschulok, Thomas; Roe, John; Whitehouse, Sarah L; Crawford, Ross
Introduction: Balanced soft tissues are important to total knee arthroplasty (TKA) outcomes. Surgical algorithms for balancing are potentially varied in varus and valgus osteoarthritic (OA) knees. While coronal plane varus knee laxity has been documented, no study has objectively defined the medial and lateral laxity of the valgus OA knee. The lower limb was manipulated at the time of TKA using computer navigation, prior to surgical releases, to allow the limb weight-bearing axis to pass through the knee center in maximum extension, 20° and 90° of flexion. The hip-knee-ankle-angle was documented at this position. Coronal plane laxity was then measured in 30 valgus (7.9 ± 4.0°) knees as medial and lateral displacement from this point and compared to published values for healthy subjects. In maximum knee extension, lateral contracture was present in 26.6% (8/30) of subjects, and abnormally lax medial tissue was present in 46.6% (14/30). Six patterns of medial versus lateral laxity were documented in maximum extension. In maximum knee extension, mean medial laxity was 7.1° (±3.8°) compared to 2.7° (±2.7°) laterally. In 20° of knee flexion, mean medial laxity was 8.5° (±3.5°) compared to 3.0° (±2.6°) laterally. In 90° of knee flexion, mean medial laxity was 3.7° (±1.3°) and 7.5° (±3.0°) laterally. A highly significant difference ( p < 0.0001) in mean laxity was demonstrated when comparing medial versus lateral values at each measurement angle and for medial versus medial and lateral versus lateral values for maximum extension and 90° of flexion. The valgus knee at the time of TKA demonstrates significant preoperative mediolateral and flexion–extension imbalance. In maximum extension, medial tissue is significantly laxer whereas in flexion this reverses and the lateral tissue is significantly laxer. We documented more patterns of medial and lateral laxity in maximum extension than advocated in prior subjective grading systems. These findings demonstrate the challenges of valgus OA knee balancing during TKA but provide, for the first time, objective measures for the starting point of this process.